Małe święto jako nośnik tożsamości kulturowej w powieści „Telluria” Władimira Sorokina - Anna Stryjakowska (Studia Rossica Posnaniensia)
The article examines the category of feast in Vladimir Sorokin’s novel Теллурия. The proposed interpretation of selected parts of the novel leads to the conclusion that in postmodern conditions, the phenomenon of small feast might take on the role of a medium of cultural identity.